Prospective Monitoring and Reporting of Adverse Drug Reactions associated with Antiplatelet and Antiepileptic Drugs in a South Indian Tertiary Care Teaching Hospital - T, Varun; J, Sebastian; A, Ramesh; MG, Narahari; Bs, Keshava; S, Harsha (Indian Journal of Pharmacy Practice)
Aprospective monitoring of adverse drug reactions associated with antiplatelet and antiepileptic drugs was carried out in a tertiary care teaching hospital. Patients diagnosed with Acute Coronary Syndrome (ACS) or ischemic stroke receiving antiplatelet drugs (Aspirin and Clopidogrel) and epileptic patients receiving antiepileptic drugs were followed for a period of six months prospectively at a tertiary care teaching hospital. WHO probability scale and Naranjo's algorithm, Modified Hartwig and Seigel scale, and Modified Shumock and Thornton scales were applied to assess the causality, severity and preventability of the reported ADRs. At the end of the study period, 15 ADRs were observed with Aspirin and 14 ADRs were observed with Clopidogrel in antiplatelet agents' class and 24 ADRs with Phenytoin and 12 ADRs with Valproic acid in antiepileptic agents' class. Among the antiplatelet agents, 82.75% of ADR's were found probable and 37.93% ADRs were possible. In antiepileptic drug class, 73.33% ADRs were found probable. In assessment of severity level, 6 ADRs were found in severity level 1 and 20 ADRs were in level 3 in severity in antiplatelet agents class and in antiepileptic drugs class 9 ADRs were found in level 1 and 23 ADRs were found level 2 severity, and 15 ADRs were found preventable in anti epileptic agents. Medications were discontinued in 14 cases and the dose was adjusted in 10 cases. Phenytoin and Sodium Valproate were found responsible for majority ADRs in Anti epileptic drugs class and Aspirin accounted for more number of ADRs in antiplatelet agents' class.
Keywords: Adverse Drug Reactions; Antiplatelets; Antiepileptic drugs